Impact of Conservation Policies on Households’ Deforestation Decisions in Protected and Open-Access Forests: Cases of Moribane Forest Reserve and Serra Chôa, Mozambique - Massinga, Jadwiga; Lisboa, Sá Nogueira; Virtanen, Pekka; Sitoe, Almeida (Frontiers in Forests and Global Change, 2022)
Tropical deforestation is considered a global priority due to its environmental, social, and economic impacts at international, national, and household levels. Conservation policies constitute one of the pathways to reverse this scenario. This paper examines the influence of forest protection measures on local communities’ livelihood decisions regarding forest clearing. It compares deforestation, access to forest resources, and households’ strategies in protected and open-access forests: the Moribane Forest Reserve (MFR) and Serra Chôa (SCH), two environmentally sensitive areas with different conservation statuses in Manica Province, central Mozambique. Socioeconomic data were collected from September 2019 to August 2020 in 149 households in MFR and 144 households in SCH. The data were cross-examined with spatial information on deforestation from 2000 to 2020. We found that conservation status impacted household strategies, leading to less income source diversification and limited commercialization of forest products. In both areas, most respondents declared unlimited access to forest resources (89.9% for MFR and 68.8% for SCH), and the remaining proportion of respondents pointed out conservation, private forest, distance, and wildlife conflict as reasons for limited access. Shifting agriculture is the unique income source for 75.2% of the families in MFR and 28.4% in SCH. Most households in SCH diversify their income by combining shifting agriculture and livestock (68.75% against 24.8% in MFR). About 97% of the sampled households in MFR cleared forest for agriculture during the period 2000–2020, while 55.6% of the households cleared the forest in SCH during the same period. In MFR, non-timber forest products are mainly for subsistence use, except honey, which is sold by 52.2% of families. In SCH, commercialization of non-timber forest products is more diverse, with 11.1% of families selling honey, bush meat (5.5%), charcoal (3.4%), medicinal plants (2%), wood (1.3%), poles (11.1%), and firewood (12.5%). We conclude that the current conservation policies have little impact on household decisions to protect the forest, but they influence income diversification, leading to more dependency on agriculture and livestock.